2013
DOI: 10.1016/j.adolescence.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of DSM‐IV mental disorders, deliberate self‐harm and suicidal ideation in early adolescence: An Irish population‐based study

Abstract: BackgroundThis study investigated the prevalence of DSM‐IV Axis 1 mental disorders, deliberate self‐harm and suicidal ideation in a sample of Irish adolescents aged 11–13 years.MethodsA total of 1131 students was surveyed for general psychopathology using the Strengths and Difficulties Questionnaire. Following this, a representative sample of 212 adolescents was assessed for mental disorders, deliberate self‐harm and suicidal ideation using the Schedule for Affective Disorders and Schizophrenia for School‐Aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Unlike other jurisdictions such as, Australia, the UK and Canada the origins of Ireland's youth mental health movement can be traced back to high levels of public concern about seemingly endemic rates of youth suicide (4th highest in Europe for 15-25 years old) (National Office for Suicide Prevention 2014) [34] and mental distress among Irish youth. Other factors propelling the movement were availability of philanthropic funding to develop mental health services in Ireland and 3 key Irish leaders from the fields of health and allied health began to drive a youth mental health agenda in both the public and political arenas.…”
Section: Current Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other jurisdictions such as, Australia, the UK and Canada the origins of Ireland's youth mental health movement can be traced back to high levels of public concern about seemingly endemic rates of youth suicide (4th highest in Europe for 15-25 years old) (National Office for Suicide Prevention 2014) [34] and mental distress among Irish youth. Other factors propelling the movement were availability of philanthropic funding to develop mental health services in Ireland and 3 key Irish leaders from the fields of health and allied health began to drive a youth mental health agenda in both the public and political arenas.…”
Section: Current Practicesmentioning
confidence: 99%
“…Latest epidemiological evidence suggests that 15.4% of 11-13 years olds [34,35] and 19.5% of 19-24 year olds [35,36] in Ireland are experiencing diagnosable mental disorders at any given time with lifetime rates of disorder as high as 56% among [19][20][21][22][23][24] year olds [37]. These findings and those from other key studies in Ireland provide sufficient evidence to leverage for a real change in youth mental health services as envisaged and advocated for by leaders in the field over many years.…”
Section: Current Practicesmentioning
confidence: 99%
“…For example, research with a representative sample of adolescents in the USA estimated a lifetime prevalence rate of 14% for mood disorders (Merikangas et al, 2010). An Irish population-based study in adolescents aged 11-13 years detected high levels of mental disorder symptomatology, with MDD featuring among the leading current and lifetime disorders (Coughlan et al, 2014). Notably, a similar but earlier study demonstrated that Irish youth faced significant mental health issues, with 10% being at risk for affective disorders (Lynch, Mills, Daly, & Fitzpatrick, 2006).…”
Section: Introductionmentioning
confidence: 86%
“…A further, more recent report estimates the prevalence of current depression as 30% among 12-to 19-year-olds (Dooley & Fitzgerald 2012). Lifetime prevalence of mental health problems among young adolescents (aged 11-13 years) in Ireland is reportedly as high as 36.8% (Coughlan et al 2014). At the same time, many young people experiencing mental health problems do not access formal support services.…”
Section: Introductionmentioning
confidence: 99%